Pemberdayaan Ibu Hamil melalui Literasi Buku KIA dalam Upaya Deteksi Dini dan Pencegahan Komplikasi Kehamilan di Klinik Pratama Sarfina Kota Medan - Sonia Novita Sari; Sri Murtini; Nova Isabella Mariance Br Napitupulu; Leni Oktafianti; Kezia S.A. Rajagukguk; Nabila Rara Putri; Azahra Azahra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The Maternal Mortality Rate (MMR) is primarily caused by pregnancy complications that are actually preventable through early detection; however, maternal understanding of the Maternal and Child Health (MCH) Handbook remains very low. This community service aims to empower pregnant women at Sarfina Primary Clinic, Medan, by enhancing their MCH Handbook literacy. The implementation utilized a Community-Based Participatory Action (CBPA) approach conducted over four weeks, involving 30 pregnant women. The activity stages included a pre-test, interactive education, self-assessment simulations, and a post-test. Evaluation results indicated a significant surge in health literacy; pregnant women's knowledge in the